Mashākil Taʻlīm al-Lugah al-ʻArabiyyah fī Indūnīsiyya - Ahmad Sayuthi Nasution (Al-Zahra : Journal for Islamic and Arabic Studies, 2005)
The teaching of Arabic language in Indonesia is dealing with some problems, including methodological issues, or the absent of an appropriate methods in teaching of Arabic language, lack of trained Arabic teachers and media of teaching. In order for the process of Arabic teaching in Indonesia runs well and succeed, we must consider some of the following points: Pay attention to the teachers’ capabilities and provide them training, analyze the mistakes to determine the level of difficulty faced by the students of Indonesia, apply teaching methods that are appropriate with the lessons character and the surround circumstances and use certain educative facilities during the teaching process.